Empirically Observed Iconicity Levels of English Phonaesthemes - Kwon, Nahyun (Public Journal of Semiotics, 2017)
This paper aims to reveal to what extent the diagrammatic iconicity (i.e., form-meaning correspondences which are created by relating similar sets of forms with similar sets of meanings [Peirce, 1955, p. 104]) of English phonaesthemes (e.g., gl- in glitter, glisten, and glow) could manifest primary iconicity (i.e., iconicity that involves a sufficient similarity between sign and referent to allow the understanding that the former stands for the latter [Sonesson, 1997]). To serve the aim, the current research conducts a test, using a multiple-choice task in which groups of native English and Korean speakers choose the meanings of phonaesthemes in sets of aurally-presented nonsense English phonaesthemic words. If primary iconicity is carried by a phonaestheme, then both native and non-native listeners should be able to report with some consistency the putative meaning of the nonsense phonaesthemic words. If, on the other hand, a form-meaning correspondence is carried by secondary iconicity (where the existence of the sign-relation, given by convention or by being explicitly pointed out, is the precondition for noticing the similarity between sign and referent [Sonesson, 1997]), then neither language group is expected to deliver high correct guessing rates. The result showed that the purported meanings of sk- and tw- were correctly guessed by the Korean-speaking participants only, and those of cl-, gl-, sw-, gr-, sn-, and sq- were correctly guessed by the English-speaking participants only. The purported meanings of sp- and tr- were correctly guessed by neither language group. These findings show that individual phonaesthemes possess varying degrees of (primary) iconicity.